The Association between Income Status and Treatment Selection for Prostate Cancer in a Universal Health Care System: A Population-Based Analysis. Issue 5 (28th November 2021) - Oake, Justin D.; Harasemiw, Oksana; Tangri, Navdeep; Ferguson, Thomas W.; Saranchuk, Jeff W.; Bansal, Rahul K.; Drachenberg, Darrel E.; Nayak, Jasmir G.
Abstract : Purpose: Treatment selection for localized prostate cancer is guided by risk stratification and patient preferences. While socioeconomic status (SES) disparities exist for access to care, less is known about the effect of SES on treatment decision-making. We sought to evaluate whether income status was associated with the treatment selected (radical prostatectomy [RP] vs radiation therapy [RT]) for nonmetastatic prostate cancer in a universal health care system. Materials and Methods: All men from Manitoba, Canada who were diagnosed with nonmetastatic prostate cancer between 2005 and 2016 and subsequently treated with RP or RT were identified using a provincial cancer database. SES was defined as neighborhood income by postal code and divided into income quintiles (Q1–Q5, with Q1 the lowest quintile and Q5 the highest). Multivariable logistic regression nested models were used to compare whether SES was associated with treatment type received. Results: We identified 3, 966 individuals who were diagnosed with nonmetastatic prostate cancer and were treated with RP (2, 354) or RT (1, 612). After adjusting for demographic and clinicopathological characteristics, as income quintile increased, men were incrementally more likely to undergo RP than RT (range Q2 vs Q1: adjusted OR 1.40, 95% CI 1.01–1.93; Q5 vs Q1: adjusted OR 2.30, 95% CI 1.70–3.12). Conclusions: As income levels increased there was a stepwise incremental increase in the odds of receiving RP over RT for localized prostate cancer. These results may inform initiatives to better understand the values, priorities and barriers that patients experience when making treatment decisions in a universal health care system.